Antimalarial Activity of C-10 Substituted Triazolyl Artemisinin - Park, Gab-Man (Korean J Parasitol, 2017)
We synthesized C-10 substituted triazolyl artemisinins by the Huisgen cycloaddition reaction between dihydroartemisinins (2) and variously substituted 1, 2, 3-triazoles (8a-8h). The antimalarial activities of 32 novel artemisinin derivatives were screened against a chloroquine-resistant parasite. Among them, triazolyl artemisinins with electron-withdrawing groups showed stronger antimalarial activities than those shown by the derivatives having electron-donating groups. In particularly, m-chlorotriazolyl artemisinin (9d-12d) showed antimalarial activity equivalent to that of artemisinin and could be a strong drug candidate.